FENOMENA KEKERASAN ANAK DALAM POLA ASUH ORANG TUA (Analisis Gender Terhadap Keluarga Di Kelurahan Tanjung Pinang) - Fersa Rahmad Dani (Journal SOSIOLOGI, 2019)
This study aims to look at how child abuse occurs in the family in Tanjung Pinang Kelurahan, as well as the causes of child abuse, what factors are behind the violence perpetrated by parents against children, violence in families also occurs, especially victims not only women but also children who are still taken care of by parents. The family is a place where children get protection, they should not get physical or psychological violence, this research methodology uses descriptive qualitative, with data collection techniques namely observation, interviews and documentation, violence in the sense of Galtung that is as a barrier that should be avoided that causes a person unable to actualize itself fairly and violently as any physical, emotional, verbal, institutional, structural or spiritual condition other than as a behavior, attitude, policy, or condition that weakens, dominates or destroys itself and others. The selection of researcher informants was done by means of snowbaal sampling. Data sources used are primary data and secondary data. Primary data obtained from observations and interviews of 8 informants and secondary data obtained from documents relating to research Data analysis techniques carried out at the time of the study are data reduction, data review and conclusion drawing, the research results are known that in the family in Tanjung Pinang Kelurahan there is still an understanding of parenting children with violence, parents especially mothers of children, there are still those who use physical and psychological violence as a way to give punishment to children, such as children against the words of parents, indifferent to the words of parents and difficult to regulate, so that the punishment that can be beaten using sticks, pinched by hand and get scolding and anger from parents as punishment for mistakes made by children in the Tanjung Pinang Kelurahan, parents also still there are differences in treatment in parenting like a boy is considered such as women when crying, the existence of parents who are harder on boys than girls, and there are time restrictions that are done by parents against girls than boys.